Democratisering in België : een verhaal zonder einde. - Van den Wijngaert, Mark; Celis, Karen; Van de Perre, Stijn; Veraghtert, Karel; Vander Weyden, Patrick (Antwerpen : Standaard, 2007)
Bibliotheek François Vercammen
Nederlands
Monografie